1991
DOI: 10.1038/354066a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a functional serotonin transporter from rat brain

Abstract: Selective antagonism of serotonin (5-hydroxytryptamine, 5HT) and noradrenaline transport by antidepressants is a key element in the 'amine' hypothesis of affective disorders. Uptake and/or transport sites of 5HT have been reported to be reduced in platelets of patients suffering from depression and in post-mortem brain samples of depressed patients and suicide victims. To date there has been little molecular information available on the structure and regulation of 5HT transporters. Using the polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
386
1
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 756 publications
(402 citation statements)
references
References 34 publications
14
386
1
1
Order By: Relevance
“…As an integral membrane protein belonging to the Na + /Cl À -dependent transporter family (Amara and Kuhar, 1993), the SERT is chiefly responsible for terminating the action of 5-HT released into the synaptic cleft (Blakely et al, 1991;Hoffman et al, 1991;Rudnick and Wall, 1992). Molecular studies indicate that the SERT consists of 630 amino acids, has 12 transmembrane domains, and that its C-and Nterminal regions lie in the cytoplasm (Tate and Blakely, 1994;Qian et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As an integral membrane protein belonging to the Na + /Cl À -dependent transporter family (Amara and Kuhar, 1993), the SERT is chiefly responsible for terminating the action of 5-HT released into the synaptic cleft (Blakely et al, 1991;Hoffman et al, 1991;Rudnick and Wall, 1992). Molecular studies indicate that the SERT consists of 630 amino acids, has 12 transmembrane domains, and that its C-and Nterminal regions lie in the cytoplasm (Tate and Blakely, 1994;Qian et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For 5-HT 1A probes, one oligonucleotide corresponding to base pairs 1110-1151 was used (Neumaier et al, 2000). For SERT probes, two oligonucleotides corresponding to base pairs 101 to 149 and 570 to 618 of the rat serotonin transporter sequence were used (Blakely et al, 1991). Probes were individually labeled with γ[ 33 P]-dATP (Amersham Biosciences, Piscataway, NJ, USA) using terminal deoxyribonucleotidyl transferase (Promega, Madison, WI, USA) and purified on NENSORB columns (Dupont NEN Research Products, Boston, MA).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The 5-HTT is also a major target for many antidepressant drug treatments (Blakely et al 1991;Ramamoorthy et al 1993). It is well known that the serotonin reuptake inhibitor (SRI) class of antidepressants increase concentrations of serotonin in the synapse by blocking the serotonin transporter (5-HTT) (Blakely et al 1991;Ramamoorthy et al 1993). However, given the time lag between the initial inhibitory effects of antidepressants on the 5-HTT and an observable improvement in symptoms of depression, the mechanisms underlying the therapeutic effects of these drugs are likely to occur downstream of 5-HTT inhibition (Blier et al 1990;Chaput et al 1991;Duman 1998;Manji et al 2001).…”
Section: -Htt ϫ / ϫ Mice On the C57bl/6j Background Showed No Baselimentioning
confidence: 99%
“…Moreover, a number of studies have found an association between genetic variation in the regulatory region of the 5-HTT gene and depression (e.g., Battersby et al 1996;Collier et al 1996a,b;Furlong et al 1998;Rees et al 1997;Menza et al 1999; but see Seretti et al 1999). The 5-HTT is also a major target for many antidepressant drug treatments (Blakely et al 1991;Ramamoorthy et al 1993). It is well known that the serotonin reuptake inhibitor (SRI) class of antidepressants increase concentrations of serotonin in the synapse by blocking the serotonin transporter (5-HTT) (Blakely et al 1991;Ramamoorthy et al 1993).…”
mentioning
confidence: 99%